A Recently Discovered Portrait of Ladislas Vasa as the Pretender to the Muscovite Throne (ca. 1609) in the Collection of the Bibliothèque nationale de France - Jacek Żukowski (Biuletyn Historii Sztuki, 2025)
The subject of this study is an analysis of a unique engraving preserved in the Bibliothèque Nationale de France depicting Prince Ladislas Vasa (1595–1648) as pretender to the Muscovite throne. It is here proposed that the print was probably executed c. 1611 on the order of Marshal Mikołaj Wolski, the king’s envoy to Rome. The author endeavours to reconstruct the ideological meaning of the print in the context of the so-called Muscovite iconography of Ladislas.